DNA Methylation Patterns of Ulcer-Healing Genes Associated with the Normal Gastric Mucosa of Gastric Cancers - Hong, Seung-Jin; Oh, Jung-Hwan; Jung, Yu-Chae; Kim, Young-Ho; Kim, Sung-Ja; Kang, Seok-Jin; Seo, Eun-Joo; Choi, Sang-Wook; Kang, Moo-Il; Rhyu, Mun-Gan (Journal of Korean medical science, 2010)
Recent evidence suggests that gastric mucosal injury induces adaptive changes in DNA methylation. In this study, the methylation status of the key tissue-specific genes in normal gastric mucosa of healthy individuals and cancer patients was evaluated. The methylation-variable sites of 14 genes, including ulcer-healing genes (TFF1, TFF2, CDH1, and PPARG), were chosen from the CpG-island margins or non-island CpGs near the transcription start sites. The healthy individuals as well as the normal gastric mucosa of 23 ulcer, 21 non-invasive cancer, and 53 cancer patients were examined by semiquantitative methylation-specific polymerase chain reaction (PCR) analysis. The ulcer-healing genes were concurrently methylated with other genes depending on the presence or absence of CpG-islands in the normal mucosa of healthy individuals. Both the TFF2 and PPARG genes were frequently undermethylated in ulcer patients. The over- or intermediate-methylated TFF2 and undermethylated PPARG genes was more common in stage-1 cancer patients (71%) than in healthy individuals (10%; odds ratio [OR], 21.9) and non-invasive cancer patients (21%; OR, 8.9). The TFF2-PPARG methylation pattern of cancer patients was stronger in the older-age group (> or =55 yr; OR, 43.6). These results suggest that the combined methylation pattern of ulcer-healing genes serves as a sensitive marker for predicting cancer-prone gastric mucosa.